Risk factors for lymphopenia in patients with relapsing–remitting multiple sclerosis treated with dimethyl fumarate - Morales, Fabian Sierra; Koralnik, Igor J.; Gautam, Shiva; Samaan, Soleil; Sloane, Jacob A. (Journal of neurology, 2020)
Objectives To identify risk factors for DMF-induced lymphopenia and characterize its impact on T lymphocyte subsets in MS patients. Methods We performed a retrospective analysis of 194 RRMS patients treated with DMF at the Beth Israel Deaconess Medical Center (BIDMC) over a median of 17 months. We reviewed demographics, ethnic background, prior medication history, complete blood counts and T lymphocyte subsets. Possible lymphopenia risk factors examined included age, prior natalizumab exposure, vitamin D levels, and concomitant exposure to carbamazepine, opiates, tobacco, or steroids. Lymphopenia was defined as grade 1: absolute lymphocytes count (ALC) 800–999/μl; grade 2: ALC 500–799/μl; grade 3: ALC 200–499/μl; and grade 4: ALC < 200/μl. Results Of 194 DMF-treated patients, 73 (38%) developed lymphopenia and reached an ALC nadir after a median of 504 days (range 82–932). Risk of developing DMF-induced lymphopenia increased with BMI 25–30, older age, white ethnicity, non-smoking status, and lowest quartile baseline ALC. Prior exposure to natalizumab or concomitant steroid, opiates or carbamazepine/oxcarbamazepine use was not associated with lymphopenia. Compared to baseline levels, CD8 T cells were significantly more reduced than CD4 cells. CD8 counts were more commonly reduced with age or white ethnicity. Subjects with BMI 25–30 was associated with a higher risk of abnormal CD4 cell count reductions. In contrast, non-smokers were more likely to experience reductions in both CD4 and CD8 counts while on DMF. Conclusions Patients with low baseline lymphocyte counts, with intermediate BMI, with white ethnicity, with advanced age, or with no tobacco use, had a significantly higher incidence of lymphopenia on DMF. Intermediate BMI or lowest quartile baseline ALC predicted low CD4 levels, while advanced age or white ethnicity predicted low CD8 levels from DMF exposure.